2016
DOI: 10.1136/bmjopen-2016-013059
|View full text |Cite
|
Sign up to set email alerts
|

Are differences in travel time or distance to healthcare for adults in global north countries associated with an impact on health outcomes? A systematic review

Abstract: ObjectivesTo investigate whether there is an association between differences in travel time/travel distance to healthcare services and patients' health outcomes and assimilate the methodologies used to measure this.DesignSystematic Review. We searched MEDLINE, Embase, Web of Science, Transport database, HMIC and EBM Reviews for studies up to 7 September 2016. Studies were excluded that included children (including maternity), emergency medical travel or countries classed as being in the global south.SettingsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
316
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(358 citation statements)
references
References 106 publications
12
316
7
Order By: Relevance
“…The impact of travel distance on patient outcomes has been examined before for other indications and elegantly summarized in a systematic review by Kelly et al 12 Over three-quarters of the examined studies demonstrated a distance-decay association with worse outcomes in individuals living further away from healthcare facilities. In our study, distance from the referral hospital was associated with greater need for surgery, immunomodulator, and biologic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of travel distance on patient outcomes has been examined before for other indications and elegantly summarized in a systematic review by Kelly et al 12 Over three-quarters of the examined studies demonstrated a distance-decay association with worse outcomes in individuals living further away from healthcare facilities. In our study, distance from the referral hospital was associated with greater need for surgery, immunomodulator, and biologic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies examining the impact of distance from a hospital have focused on medical or surgical emergencies, demonstrating that in three-quarters of such studies, there existed a “distance decay” relationship with worse outcomes in patients living further away from the site of care. 12 One can envision that distance from care may also be relevant in diseases like IBD that are beset by unpredictable flares, requires periodic clinical and endoscopic evaluation to ensure remission, and rely on long-term adherence to therapy that requires a regular patient-provider relationship. Consequently, we performed this study with aim of examining the impact of distance from area of residence to a referral IBD center on the need for surgery and biologic therapy in patients with CD and UC.…”
Section: Introductionmentioning
confidence: 99%
“…Travel distance has also been associated with unsuccessful transition from pediatric to adult sickle cell disease centers [16]. In adults, the majority of studies have shown worse health outcomes, including follow-up non-attendance, for patients living further away from healthcare facilities [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The need to travel is often produced by the fact that cancer care is offered in specialist centres, which are not always located close to patients' place of residence (2,3). Patients might need to travel to have all of their care in specialist centres or only for specific aspects of their treatment (i.e., surgery) (4). In some instances, patients and their families might choose to travel and relocate to access care in hospitals they believe can provide a higher quality of care (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in-depth analysis of patients' and carers' views and experiences of travel during treatment is required to inform and shape care delivery. Some reviews have explored travel for cancer care, but these have mainly focused on the impact of travel time and distance to a specialist centre on patients' choice, access, adherence to treatment and outcomes (4,15,16). Travel costs have also been explored, but normally in relation to treatment delays or interruptions (15).…”
Section: Introductionmentioning
confidence: 99%